Kritik Ekonomi Islam Terhadap Mekanisme Distribusi Pendapatan Dalam Sistem Ekonomi Kapitalis - Hidayatun Azizah (Fakultas Ekonomi dan Bisnis Islam IAINU Kebumen, 2019)
The system of free-market as a modern society system, in reality, does not fully prop prosperity up for society. This as if contradicts to Invisible Hand theory of Adam Smith becoming background of free-market system. In one hand, it cannot be denied that the free-market system has helped the achievement of economic growth rapidly. But, in another hand, that growth is not gathered with equalization so it causes the social imbalance and discrepancy. In fact, the benefit of free-market system is only taken by the investors, while the poor people must allow their power to be sold to the investors. Therefore, by the imbalance fact of free-market system, it is proper that the existence of free-market as an income distribution mechanism is questionable. By that fact, Islamic economy offers an alternative solution due to inefficient free-market system in capitalism system. That solution is by giving government opportunity as regulator. This is urgent because by their authority, the imbalance of market mechanism can be minimized. Their actualization in the public is based on Tauhid, al-Adl, and Khilafah principle as the basic of economic interaction. In this case, the main act of government is related to the fulfillment of basic need and guarantee in achieving the spiritual values implementation in the social life.